Receiver bandwidth enhancement design for high speed optical system - Mohammad, Intan Shafinaz (2013)
The technology of optical-fiber systems is advancing rapidly. Parallel to the development of long-haul telecommunication systems in the gigabits per second data rates operating in the long-wavelength region is the wide penetration of optical-fiber systems in local area networks, video trunking and distribution, sensors, etc. These diversified applications impose different and often conflicting constraints on the optical receiver. The weakest signal level determined at the front-end receiver and it should be improved by appropriate design. The optimum receiver performance can be achieved depends on the devices and design techniques used. This project reexamines